Breastfeeding during Disaster - Donna Davis (EDIS)
“As we’ve learned over the past couple of years, disaster can strike anyone, anywhere, and anytime. A natural disaster, whether hurricane, tornado, flood, or tsunami, can devastate areas and leave families without resources, sometimes for long periods of time. And while people of all ages suffer, infants can be at far greater risk. However, mothers can save their infants’ lives and protect them from illness by simply breastfeeding, even if they haven’t been breastfeeding their baby.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, March 2012.